2021
DOI: 10.1097/bpo.0000000000001773
|View full text |Cite
|
Sign up to set email alerts
|

Late Hip Dysplasia After Normal Ultrasound in Breech Babies: Implications on Surveillance Recommendations

Abstract: Background: There is significant controversy in the literature over rates of late-developing dysplasia following normal screening ultrasound in breech babies, with reported rates varying from 7% to 29%. The purpose of this study is to investigate the rates of radiographic dysplasia in breech babies after a normal ultrasound with a minimum of 1 year of radiographic follow-up. Methods: This study was an institutional review board–approved prospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Morris et al . ( 19 ), through a prospective study, reported a rate of 2.2% radiographic dysplasia in breech babies at 12 months follow-up after a negative hip ultrasound. Another US study ( 20 ) reported a prevalence of late DDH of 10%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morris et al . ( 19 ), through a prospective study, reported a rate of 2.2% radiographic dysplasia in breech babies at 12 months follow-up after a negative hip ultrasound. Another US study ( 20 ) reported a prevalence of late DDH of 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, literature has highlighted the possibility of a "late DDH" diagnosis after a negative initial ultrasound screening in children with breech presentation (16)(17)(18)(19)(20)(21)(22). If this condition were to be confirmed, there would be a group of children for whom current screening programs might not be sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…The development of the bone and cartilage of the acetabulum is evaluated with alpha and beta angles in the Graf method. 17,18 In a Graf type 1 mature hip, the alpha angle is > 60 degrees and does not deteriorate over time. Hips with an alpha angle <50 degrees are evaluated as dysplastic hips (Type 2c, Type 2d, Type 3, and Type 4).…”
Section: Discussionmentioning
confidence: 99%
“…The development of the bone and cartilage of the acetabulum is evaluated with alpha and beta angles in the Graf method 17,18. In a Graf type 1 mature hip, the alpha angle is >60 degrees and does not deteriorate over time.…”
Section: Discussionmentioning
confidence: 99%
“…There is extensive literature discussing the strengths of both US and plain films for the diagnosis of DDH, as well as the incidence of late-presenting dysplasia in various cohorts 11,12,19–21. Barrera et al22 discuss the various imaging techniques that are utilized over the course of treatment for DDH.…”
Section: Discussionmentioning
confidence: 99%